Cyclic Mechanical Strain Regulates Osteoblastic Differentiation of Mesenchymal Stem Cells on TiO2 Nanotubes Through GCN5 and Wnt/β-Catenin - Liu, Yanchang; Cheng, Wendan; Zhao, Yao; Gao, Liang; Chang, Yongyun; Tong, Zhicheng; Li, Huiwu; Jing, Juehua (Frontiers in Bioengineering and Biotechnology, 2021)
Bone marrow mesenchymal stem cells (BMSCs) play a critical role in bone formation and are extremely sensitive to external mechanical stimuli. Mechanical signals can regulate the biological behavior of cells on the surface of titanium-related prostheses and inducing osteogenic differentiation of BMSCs, which provides the integration of host bone and prosthesis benefits. But the mechanism is still unclear. In this study, BMSCs planted on the surface of TiO2 nanotubes were subjected to cyclic mechanical stress, and the related mechanisms were explored. The results of alkaline phosphatase staining, real-time PCR, and Western blot showed that cyclic mechanical stress can regulate the expression level of osteogenic differentiation markers in BMSCs on the surface of TiO2 nanotubes through Wnt/β-catenin. As an important member of the histone acetyltransferase family, GCN5 exerted regulatory effects on receiving mechanical signals. The results of the ChIP assay indicated that GCN5 could activate the Wnt promoter region. Hence, we concluded that the osteogenic differentiation ability of BMSCs on the surface of TiO2 nanotubes was enhanced under the stimulation of cyclic mechanical stress, and GCN5 mediated this process through Wnt/β-catenin.